Albumin abundance and its glycation Status determine hemoglobin glycation - Jagadeeshaprasad, Mashanipalya G.; Venkatasubramani, Vinashya; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2018)
Diabetes diagnosis and management majorly depend upon the measurement of glycated hemoglobin (HbAlc) levels. Various factors influence HbAlc levels such as the use of various analytical methods and the presence of various clinical conditions. Plasma albumin levels were known to be negatively associated with HbAlc. However, the precise mechanism by which they affect HbAlc is not well' understood. Therefore, we have studied the influence of albumin levels and its glycation status on hemoglobin glycation using erythrocyte culture experiments. Erythrocytes maintained at low albumin concentration exhibited relatively increased albumin and hemoglobin glycation as compared to that in those maintained at higher albumin concentration. Increase in albumin glycation may decrease its ability to protect hemoglobin glycation. This was demonstrated by treatment of erythrocytes with N(epsilon-(carboxymethyl)lysine-modified serum albumin (CMSA), which failed to protect hemoglobin glycation; instead, it increased hemoglobin glycation. The inability of CMSA to reduce hemoglobin glycation was due to the lack of free lysine residues of albumin, which was corroborated by using N(epsilon-(acetyI)lysine serum albumin (AcSA) and clinical diabetic plasma. This is the first study which demonstrates that the modification of lysine residues of albumin impairs its ability to inhibit hemoglobin glycation. Furthermore, correlation studies between HbAlc and albumin levels or relative albumin fructosamine from clinical subjects supported our experimental finding that albumin abundance and its glycation status influence hemoglobin glycation. Therefore, we propose albumin level and its glycation status to be quantified in conjunction with HbAlc for better management of diabetes.